Macrophages as Emerging Key Players in Mitochondrial Transfers - Pang, Yidan; Zhang, Changqing; Gao, Junjie (Frontiers in Cell and Developmental Biology, 2021)
Macrophages are a group of heterogenous cells widely present throughout whole body. Under the mutual influence of macrophages and their specific environments via both contact and non-contact signals, macrophages integrate into host tissues and contribute to the tissue development and functions of tissue cells. As an essential organelle, mitochondria exert intercellular transfer for regulating cell homeostasis. Our review focuses on newly discovered roles of mitochondrial transfers between macrophages and their surrounding cells to summarize emerging functions of macrophages in transmitophagy, metabolic regulation and immune defense. We also discuss the negative influence of mitochondrial transfers on macrophages and current therapies targeting mitochondria in macrophage. Regulating macrophages through mitochondrial transfers between macrophages and surrounding cells can be promising therapy for various diseases including cardiovascular diseases, inflammatory diseases, obesity and cancer.